Development of Learning Media 'Electric Circuit Teaching Aid' as an Effort to Increase Learning Motivation of Class V and VI Students of Wasur I State Elementary School - Helga Charolina A. Silubun; Ivylentine Datu Palittin (Budapest International Research and Critics University, 2022)
This research is to find out development of learning media 'electric circuit teaching aid' as an effort to increase learning motivation of class V and VI students of Wasur I State Elementary School. This research method uses analysis, design, development, implementation, and evaluation (ADDIE) procedures. The teaching aids developed are a series of series and parallel circuit boards, which have been validated by 2 expert validators and 2 user validators, namely teachers. The teaching aids were then demonstrated in natural science learning with the theme of electric circuits for class V and VI students of Wasur I State Elementary School, Wasur Village, Merauke District, Papua, in August to December 2021. From the research results obtained an average value of 4.33 validation is in the range of scores of 4.22 and 5, included in the very feasible criteria, with the average percentage result is 86.66%. The results of observations and interviews showed that students were motivated during the learning process using the media.